Model Kepemimpinan Pendidikan Profetik Nabi Muhammad SAW - Diah Robiatul Adawiah; Machdum Bachtiar; Eneng Muslihah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
As a Muslim, you should use the Quran and Hadith as an example in your life. Every leader stands on the idea of leadership in accordance with Islam. The leadership of the Prophet (propetik) is the best example of leadership. This study aims to find a prophetic leadership model in the world of Islamic education. This research is a Qualitative Research with a literature study approach. The data collected from this study came from relevant literature sources. This study shows that the essence of prophetic leadership is that a leader must reflect the values, principles of life, and character of the Prophet namely shiddik (right), trustworthy (trustworthy).